Encyclopedia of social theory - Harrington, Austin; Marshall, Barbara L.; Müller, Hans-Peter (Routledge, 2006)
"The Encyclopedia of Social Theory provides a reference source for students and academics, embracing all major aspects of the field. Written by more than 200 internationally distinguished scholars, almost 500 entries cover core contemporary topics, concepts, schools, debates, and personalities in the history of the discipline. Special attention is paid to leading schools and debates, with shorter entries reserved for biographies of key theorists and definitions of key terms. Entries are fully cross-referenced and contain concise listings for further reading. A comprehensive index guides the reader to further divisions of contents."--BOOK JACKET
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Wörterbuch; Philosophie; Soziologie; Soziologische Theorie